An identification of second language learners errors in classifying nouns, verbs, and adjectives - Subramaniam, Vijayaletchumy; Nagaraju, Pavitira; Nik Muhamad Affendi, Nik Rafidah (Seybold Publications, 2023)
In this study, we aimed to recognize the students mastery in determining the word classes of nouns, verbs, and adjectives and analyzed the errors made by the students during the process. A total of 117 excellent Year 6 students from 20 different Tamil vernacular schools “ SJK(T) in Kuala Selangor district were selected as research samples. We used quantitative approach in this study. Written test was conducted to determine the students understanding in grouping the word classes for each word. In addition, Corders Language Error Analysis Theory (1981) comprised of five steps was used to pinpoint the students mistakes made during the categorization of word classes. Based on the findings, the students ignorance of the existence of affix is the most common mistake made in the classification of word classes especially for nouns and verbs. A large number of students assumed that nouns with affix is always verb. The lacking of knowledge on the selection of noun affixes is one of the problems faced by the learners in identifying the word classes. Other than that, learners often failed to describe adjective in context or picture, misuse of the affixation conceptand their lacking of vocabulary in adjectives also showed the weakness of the students in illustrating the word classes for a word. In conclusion, the overall results showed that the mastery level of students in determining the word classes is not up to par. Thus, a robust technique is in need for the learners to help them identifying the word classes of the word clearly and precisely.